A megakaryocyte in the peripheral blood: evidence for pulmonary migration? - Kennedy, Stephanie Juané (Frontiers in Hematology, 2025)
Pulmonary megakaryocytes were first identified over a century ago, but their origin is still debated. Two rare images of circulating megakaryocytes are presented to illustrate this discussion: The first shows an intact megakaryocyte with abundant cytoplasm and a hyperlobulated nucleus on a peripheral smear made from blood drawn through a Hickman line in a child with B-cell acute lymphoblastic leukaemia. The morphology of this megakaryocyte is contrasted with that of the second image, from a patient with primary myelofibrosis. This perspective focuses on the first image, which illustrates several hypotheses regarding the origin and function of pulmonary megakaryocytes. According to the most widely accepted theory, this megakaryocyte may have originated in the bone marrow (BM), entered the venous circulation, and migrated to the lungs, where it was aspirated from the superior vena cava before being trapped in the pulmonary vasculature to exert its incompletely understood functions. In this child with acute leukaemia, it could have been a role-player the cancer immune response. Alternatively, pulmonary megakaryocytes may have been compensating for the displacement of platelet-producing megakaryocytes by blasts in the BM. While a single anecdotal image cannot provide mechanistic evidence, this megakaryocyte, when interpreted in its clinical context, provides visual support for (1) the hypotheses that at least some pulmonary megakaryocytes have a BM origin, (2) the theory that lung megakaryocytes may augment platelet production during thrombocytopenic states, and (3) chemotherapy-induced megakaryocyte release from the BM. It serves as a reminder that we should continue to draw insights from clinical observations.